ANALISIS GEOTEKNIK TANAH LEMPUNG TERHADAP PENAMBAHAN SERBUK CANGKANG TELUR DAN GIPSUM - Khairunnisa Khairunnisa; Ellida Novita Lydia; Eka Mutia (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
Clay soil is characterized by fine grains, low bearing capacity, and high shrinkage levels, making it unsuitable for construction work. Therefore, soil improvement is necessary to enhance the CBR (California Bearing Ratio) value and increase its bearing capacity. This research aims to identify the optimal percentage and impact of adding eggshell powder and gypsum on the CBR value of clay soil. The study employs an experimental method, mixing varying percentages of eggshell powder (2%, 4%, 6%, 8%) with a constant 10% gypsum. Tests on soil's physical and mechanical properties, such as water content, specific gravity, Atterberg limits, sieve analysis, compaction, and CBR, were conducted. The findings show that the optimal CBR value was achieved with a mix of 84% clay, 6% eggshell powder, and 10% gypsum, resulting in a CBR penetration of 2.223% at 0.1